Indonesia Development Policy Report : Beyond Macroeconomic Stability - World Bank (Washington, DC, 2013)
The year 2004 will mark another crucial step in Indonesia's long-term transition. The country will go to the polls to elect new national and regional Parliaments, and for the first time in the history o f the Republic, to directly elect a President. This milestone in the country's democratization is accompanied by one in economic policy: for the first time since the onset o f the crisis, the Government will not have a program supported by the IMF. The Government's decision to graduate from its IMF program is warranted by the strong improvements in the country's macroeconomic conditions, and has been broadly welcomed by the markets and the international community. The Government's "Economic Policy Package Pre and Post IMF" or White Paper, issued as a presidential instruction on September 15th has helped build confidence in the Government's policies in the election year ahead. The policy package is intended to "bridge the credibility gap." The White Paper is a unique document: it is the first time that the Government commits itself transparently to a time-bound action plan to implement policies. The document shows continuity in macroeconomic policies and financial sector reforms, but also proposes a set of specific policy and institutional measures to address issues that have undermined the country's investment climate. While the timetable for adopting these measures is a short term one - fifteen months - many o f the proposed measures address fundamental longer term problems, and some will take several years to see through fully. The private sector, which has a high " stake in the measures included in the paper, has emerged as an independent monitor of progress. Since the White Paper is so central to Indonesia in the year ahead, much of this brief is devoted to discussing it. Beyond recent developments, the report discusses and analyzes critical policy actions from the White Paper. The report also points at the White Paper measures that may not necessarily be in line with the stated goals of the document. And finally, the report identifies policies that are needed beyond the White Paper to ensure Indonesia builds on the macroeconomic stability achieved to attain more rapid growth and poverty reduction.